A new species of Magneuptychia Forster, 1964 (Lepidoptera: Nymphalidae: Satyrinae) from Brazilian Savanna - Zacca, Thamara; Siewert, Ricardo R.; Mielke, Olaf H. H.; Casagrande, Mirna M. (Zootaxa, 2014)
A new species of Satyrinae butterfly from the Brazilian Savanna, Magneuptychia flavofascia n. sp., is described based on adult morphological characters with a discussion about its placement within the genus.